دور الإصلاحات التشريعية والقانونية في تحسين مناخ الاستثمار ، التجربة الفيتنامية نموذجا. - بوخاتم، لخضر (المركز الجامعي المقاوم الشيخ أمود بن مختار -إيليزي-, 2024)
الملخص: هدفت هذه الدراسة لتعرف على مفهوم الاستثمار ودوره في عملية تحقيق التنمية الاقتصادية ومعرفة أبرز العوامل والمتطلبات التي تؤثر في عملية جذب الاستثمارات، حيث تم التركيز على الجانب التشريعي والقانوني كمدخل رئيسي في تحسين من بيئة الأعمال وجذب الاستثمارات، أين تم عبر هذه الدراسة اختيار النموذج الفيتنامي كواحد من أهم النماذج العالمية التي شهدت نجاحا باهرا في تنفيذ إصلاحات شاملة ساهمت في جعل البلاد وجهة استثمارية كبرى. وخلصت الدراسة عبر تتبع وتحليل مختلف التعديلات، البيانات والإحصائيات إلى نجاح فيتنام في تطبيق مجموعة من الاستراتيجيات والإصلاحات خاصة تلك المتعلقة بالجوانب القانونية والتشريعية في تحسين بيئة الأعمال وتحفيز المستثمرين على اختيار فيتنام كوجهة استثمارية لمشاريعهم المتنوعة، وجاءت تلك الإصلاحات لتساعد على تحقيق التنمية بالتوازي مع إصلاحات أخرى على غرار البنية التحتية، تأهيل الموارد البشرية . الكلمات المفتاحية: الاستثمار، قانون الاستثمار، التنمية، فيتنام Abstract This study aimed to explore the concept of investment and its role in driving economic and social development. It also sought to identify the key factors and requirements that influence the attraction of investments, with a specific focus on the legislative and legal aspects as crucial elements in improving the business environment and attracting investments. The study selected the Vietnamese model as one of the most successful global models in implementing comprehensive reforms, making the country a major investment hub. The study concluded after tracking and analyzing various reformes, data, and statistics that Vietnam's success in implementing a range of strategies and reforms, especially those related to legal and legislative aspects, has improved the business environment and incentivized investors to choose Vietnam as an investment destination for their diverse projects. These reforms are helping to achieve development alongside other reforms in infrastructure, human resource development. Keywords: Investment, investment law, development, Vietnam